A modern-day requirement for co-ordinated covert action - Cormac, Rory; Goodman, Michael S.; Tom, Holman (Taylor & Francis, 2016)
Covert action can be an important weapon in a state’s arsenal. It is, however, inherently controversial and risky. Rory Cormac, Michael S Goodman and Tom Holman argue that when considering covert action, Whitehall should look to lessons from the recent past. The UK has long used covert action, and how best to manage and co-ordinate such sensitive activity was for many decades a key preoccupation of its policy-makers and politicians. Given the secrecy involved, these lessons, and the machinery created, have been lost to history. Yet with covert action seemingly now back on the agenda, previous experience and hard-learnt lessons have assumed renewed importance.